Performance of lactating dairy cattle housed in a four-row freestall barn equipped with three different cooling systems - Smith, John F., 1962-; Harner, Joseph P.; Pulkrabek, B. J.; McCarty, D. T.; Brouk, Michael J.; Shirley, John E. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Ninety-three multiparous Holstein cows averaging 130 days in milk (DIM) were utilized to evaluate three cooling treatments installed in separate pens of a four-row freestall barn in northeast Kansas during the summer of 1999. Treatments were: 1) a double row of 36-inch fans spaced at 24-ft intervals over the freestalls; 2) a single row of 36-inch fans spaced at 24-ft intervals over the freestalls and over the cow feed line; and 3) a double row of 36-inch fans spaced at 24-ft intervals over the freestalls and a single row over the feed line. Each pen was equipped with identical sprinkler systems over the cow feed line. The 85-day study evaluated milk production, body condition score, respiration rate, and feed intake of cows cooled with the systems. Cows cooled with fans over the freestalls and feed line produced more (P< .05) milk (98.8 vs 93.9 lb/cow/day) than those cooled with fans only over the freestalls. Milk production was similar for cows cooled with fans over the freestalls and feed line, and doubling the number of fans over the freestalls had no apparent advantage. Cows in all treatments consumed similar amounts of feed, and those cooled only by fans over the freestalls tended to gain more body condition than cows in the other two treatments. Estimated increase in net income realized from using these cooling systems ranged from $3,500-6,100/year/pen.
Keywords: Dairy; Environmental stress; Heat Stress; Milk production